Mathematical Representation Ability of Algebraic Form Material of Class VII Students at SMPN 7 Makassar - Rusli, R.; Dassa, Awi; Pebrianty, Nurafni; Musa, Hastuty (ARRUS Journal of Mathematics and Applied Science, 2024)
This study aims to determine how the mathematical representation ability of seventh grade students at SMPN 7 Makassar in solving algebraic form problems. This type of research is qualitative research with a descriptive approach. The subjects of this study were 3 students from class VII.8 SMPN 7 Makassar in the 2021/2022 academic year. The focus of this research is the ability of visual representation, symbolic representation (mathematical expression) and verbal representation. The instruments used in data collection are mathematical representation ability test questions and interview guidelines. The results showed that: (1) Representation ability on visual indicators is moderate. The three subjects were able to present images of the given story problems but the subjects still had difficulty in presenting images of the given mathematical symbols. (2) Mathematical representation ability on mathematical expression indicators is low. There are 2 subjects who are able to solve problems involving mathematical expressions but the three subjects have not been able to create equations or mathematical models from other given representations. (3) Mathematical representation ability on verbal indicators is quite high. On average, subjects were able to solve problems by presenting statements using everyday language from the given mathematical equations even though there were still subjects who were mistaken in solving the problem.